Considerations on analogue to digital converter architectures for EEG acquisition in Augmented Cognition applications - Casson,AJ; Rodriguez-Villegas,E (Human Factors and Ergonomics Society, 2008)
Analogue to Digital Conversion (ADC) forms an essential part of EEG systems allowing signals to be represented in the digital domain and processed by a computer. For wearable, battery powered applications, such as those envisioned in augmented cognition, power consumption is a key design parameter. This paper investigates the ADC specifications that are used for typical augmented cognition applications and links these to a review of ADC topologies and performance. It is found that the ADC power consumption is an exponential function of the resolution of the ADC, but that the resolution required is often over estimated. Also, care is required when considering oversampling converters to ensure that the power consumption of decimation is accounted for.